Protein purification in chromatographic media using multiwall carbon nanotubes - NM, Mubarak; Yusof, Faridah (OMICS International - Open Access Publisher, 2015)
Carbon Nanotubes (CNTs) had been synthesized by Double Stage Chemical Vapor Deposition (DS-CVD) at the gas phase with Hydrogen gas (H2) and acetylene (C2H2) as precursor gases. Moreover, the structure of CNTs, morphology and purity were characterized by using the Transmission Electron Microscope (TEM), Field Emission Scanning Electron Microscope (FESEM) and Thermogravimetric Analysis (TGA). Furthermore, the best conditions for the optimal CNT was reaction at temperature of 750°C, reaction time of 30 minutes, with gas flow rates H2 and C2H2 for 60 and 170 ml/min for respectively. The hydrochloric acid was used to purify produced CNT and then using the nitric acid and sulfuric treatment to functionalize. Moreover, functionalized CNTs, non-functionalized were used as column chromatographic media for skim latex protein purification. Thus, the results reveal that at pH7 and ionic strength 50 mM gives higher efficiency of protein removal from the skim latex.